2015
DOI: 10.1183/09031936.00076214
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious impact of Pseudomonas aeruginosa on cystic fibrosis transmembrane conductance regulator function and rescue in airway epithelial cells

Abstract: The epithelial response to bacterial airway infection, a common feature of lung diseases such as chronic obstructive pulmonary disease and cystic fibrosis, has been extensively studied. However, its impact on cystic fibrosis transmembrane conductance regulator (CFTR) channel function is not clearly defined. Our aims were, therefore, to evaluate the effect of Pseudomonas aeruginosa on CFTR function and expression in non-cystic fibrosis airway epithelial cells, and to investigate its impact on ΔF508-CFTR rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 42 publications
5
47
0
1
Order By: Relevance
“…Non‐CF primary hAECs were isolated from nasal tissues that were obtained from patients without lung pathology who underwent nasal surgery at Centre Hospitalier de l'Universitéal (CHUM; Montréde Montréal, QC, Canada). CF hAECs were collected from patients with CF after nasal surgery at CHUM and Sainte‐Justine hospitals (Montréal, QC, Canada), and bronchial tissues were collected from patients with CF who underwent lung transplantation (25, 29, 30), according to approved ethical protocols (Comitéd'éthique de la recherche du CHUM; CE 08.063 and HD 04.025) and with patients providing written informed consent. After recovery, tissues were rinsed and incubated for 18 h at 4°C with MEM (Thermo Fisher Scientific Life Sciences, Waltham, MA, USA) that was supplemented with 7.5% NaHCO 3 (Sigma‐Aldrich, St. Louis, MO, USA), 2 mM L‐glutamine (Thermo Fisher Scientific Life Sciences), 10 mM HEPES (Thermo Fisher Scientific Life Sciences), 0.05 mg/ml gentamycin (Sandoz, Boucherville, QC, Canada), 100 U/ml penicillin‐streptomycin, 0.25 mg/ml fungizone (Thermo Fisher Scientific Life Sciences), 0.1% protease (Sigma‐Aldrich), and 10 mg/ml DNAse (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Non‐CF primary hAECs were isolated from nasal tissues that were obtained from patients without lung pathology who underwent nasal surgery at Centre Hospitalier de l'Universitéal (CHUM; Montréde Montréal, QC, Canada). CF hAECs were collected from patients with CF after nasal surgery at CHUM and Sainte‐Justine hospitals (Montréal, QC, Canada), and bronchial tissues were collected from patients with CF who underwent lung transplantation (25, 29, 30), according to approved ethical protocols (Comitéd'éthique de la recherche du CHUM; CE 08.063 and HD 04.025) and with patients providing written informed consent. After recovery, tissues were rinsed and incubated for 18 h at 4°C with MEM (Thermo Fisher Scientific Life Sciences, Waltham, MA, USA) that was supplemented with 7.5% NaHCO 3 (Sigma‐Aldrich, St. Louis, MO, USA), 2 mM L‐glutamine (Thermo Fisher Scientific Life Sciences), 10 mM HEPES (Thermo Fisher Scientific Life Sciences), 0.05 mg/ml gentamycin (Sandoz, Boucherville, QC, Canada), 100 U/ml penicillin‐streptomycin, 0.25 mg/ml fungizone (Thermo Fisher Scientific Life Sciences), 0.1% protease (Sigma‐Aldrich), and 10 mg/ml DNAse (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…This broad loss in CFTR function, even in ORKAMBI ® -rescued F508del-CFTR cells, implies that a similar response to bacteria is responsible for the loss in CFTR function. It has previously been shown that expression of mature CFTR to the apical membrane decreases upon infection with P. aeruginosa bacteria [16][17][18], even in cells that were pre-treated with CFTR correctors (VX-809 or VRT-325) [17,18]. Further, Bomberger et al, have shown that outer membrane vesicles secreted from P. aeruginosa increase the degradation of apical CFTR by redirecting recycled CFTR from endosomes to lysosomes [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Low efficacy and high patient-to-patient variation in ORKAMBI ® response might feasibly be attributed, in part, to differences in types of microbial infections across patients and even within a single patient over time [14,15]. P. aeruginosa (lab strain PAO1) exposure has been shown to reduce corrector-mediated rescue (VX-809 or VRT-325) of CFTR in human bronchial epithelial cells (HBE) [16][17][18] and stimulate the expression of the pro-inflammatory cytokines, IL-6 and IL-8 [18,19]. On the other hand, 4,6,4 -trimethylangelicin (TMA), which is a dual-acting compound (CFTR corrector and potentiator), has been shown to exert its action by interacting directly with the CFTR protein, and reducing P. aeruginosa-dependent IL-8 secretion [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In CF, defective mucociliary clearance causes an accumulation of a thick mucus plugs within the airways. Such oxygen-limited environments provide the perfect niche for P. aeruginosa to thrive (Ratjen et al, 2003;Trinh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%